A question of integrity: Variants of Bt Cotton, pesticides and productivity in Pakistan - Ma, Xingliang; Smale, Melinda; Spielman, David J.; Zambrano, Patricia; Nazli, Hina; Zaidi, Fatima (Wiley, 2017)
Bt cotton remains one of the most widely grown biotech crops among smallholder farmers in lower income countries, and numerous studies attest to its advantages. However, the effectiveness of Bt toxin, which depends on many technical constraints, is heterogeneous. In Pakistan, the diffusion of Bt cotton occurred despite a weak regulatory system and without seed quality control; whether or not many varieties sold as Bt are in fact Bt is also questionable. We utilise nationally representative sample data to test the effects of Bt cotton use on productivity. Unlike previous studies, we invoke several indicators of Bt identity: variety name, official approval status, farmer belief, laboratory tests of Bt presence in plant tissue, and biophysical assays measuring Bt effectiveness. Only farmer belief affects cotton productivity in the standard production model, which does not treat Bt appropriately as damage‐abating. In the damage control framework, all Bt indicators reduce damage from pests. Biophysical indicators have the largest effect and official approval has the weakest. Findings have implications for impact measurement. For policy‐makers, they suggest the need, on ethical and productivity grounds, to improve variety information and monitor variety integrity closer to point of sale.